The biological responses and mechanisms of endothelial cells to magnesium alloy. Issue 3 (28th May 2021) - Hou, Zhe; Xiang, Maolong; Chen, Nuoya; Cai, Xiao; Zhang, Bo; Luo, Rifang; Yang, Li; Ma, Xiaoyi; Zhou, Lifeng; He, Fugui; Yu, Hongchi; Wang, Yunbing
Abstract: Due to its good biocompatibility and degradability, magnesium alloy (Mg alloy) has shown great promise in cardiovascular stent applications. Rapid stent re-endothelialization is derived from migrated and adhered endothelial cells (ECs), which is an effective way to reduce late thrombosis and inhibit hyperplasia. However, fundamental questions regarding Mg alloy affecting migration and adhesion of ECs are not fully understood. Here, we evaluated the effects of Mg alloy on the ECs proliferation, adhesion and migration. A global gene expression profiling of ECs co-culturing with Mg alloy was conducted, and the adhesion- and migration-related genes were examined. We found that Mg alloy had no adverse effects on ECs viability but significantly affected ECs migration and adhesion. Co-cultured with Mg alloy extract, ECs showed contractive adhesion morphology and decreased motility, which was supported by the down-regulation of adhesion-related genes ( Paxillin and Vinculin ) and migration-related genes ( RAC 1, Rho A and CDC 42 ). Accordingly, the re-endothelialization of Mg alloy stent was inhibited in vivo . Our results may provide new inspiration for improving the broad application of Mg alloy stents.